Arctiin-encapsulated DSPE-PEG bubble-like nanoparticles inhibit alveolar epithelial type 2 cell senescence to alleviate pulmonary fibrosis via the p38/p53/p21 pathway - Xiong, Dian; Gao, Fei; Shao, Jingbo; Pan, Yueyun; Wang, Song; Wei, Dong; Ye, Shugao; Chen, Yuan; Chen, Rui; Yue, Bingqing; Li, Juan; Chen, Jingyu (Frontiers in Pharmacology, 2023)
Background: Idiopathic pulmonary fibrosis is a severe and deadly form of diffuse parenchymal lung disease and treatment options are few. Alveolar epithelial type 2 (AEC2) cell senescence is implicated in the pathogenies of IPF. A major bioactive compound from the traditional Chinese medicine Fructus arctii, arctiin (ARC) has robust anti-inflammatory, anti-senescence, and anti-fibrosis functions. However, the potential therapeutic effects of ARC on IPF and the underlying mechanisms involved are still unknown. Methods: First of all, ARC was identified as an active ingredient by network pharmacology analysis and enrichment analysis of Fructus arctii in treating IPF. We developed ARC-encapsulated DSPE-PEG bubble-like nanoparticles (ARC@DPBNPs) to increase ARC hydrophilicity and achieve high pulmonary delivery efficiency. C57BL/6 mice were used to establish a bleomycin (BLM)-induced pulmonary fibrosis model for assessing the treatment effect of ARC@DPBNPs on lung fibrosis and the anti-senescence properties of AEC2. Meanwhile, p38/p53 signaling in AEC2 was detected in IPF lungs, BLM-induced mice, and an A549 senescence model. The effects of ARC@DPBNPs on p38/p53/p21 were assessed in vivo and in vitro. Results: Pulmonary route of administration of ARC@DPBNPs protected mice against BLM-induced pulmonary fibrosis without causing significant damage to the heart, liver, spleen, or kidney. ARC@DPBNPs blocked BLM-induced AEC2 senescence in vivo and in vitro. The p38/p53/p21 signaling axis was significantly activated in the lung tissues of patients with IPF, senescent AEC2, and BLM-induced lung fibrosis. ARC@DPBNPs attenuated AEC2 senescence and pulmonary fibrosis by inhibiting the p38/p53/p21 pathway. Conclusions: Our data suggest that the p38/p53/p21 signaling axis plays a pivotal role in AEC2 senescence in pulmonary fibrosis. The p38/p53/p21 signaling axis inhibition by ARC@DPBNPs provides an innovative approach to treating pulmonary fibrosis in clinical settings.